2014
DOI: 10.1108/afr-09-2013-0035
|View full text |Cite
|
Sign up to set email alerts
|

Domestic and foreign direct investment in Ghanaian agriculture

Abstract: Purpose – The purpose of this paper is to investigate the effects of foreign direct investment (FDI) into agriculture on domestic investment in agriculture. Design/methodology/approach – Time series data from 1976 to 2007 was fitted to a derived model. Findings – Foreign direct investment into agriculture crowd-in domestic investment into agriculture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…Similarly, Oloyede (2014) using a Granger causality test found a positive relationship between FDI and agricultural sector development in Nigeria with data that spanned from 1981 to 2012. Other research works showed a positive relationship between FDI and agricultural output includes Kareem et al (2013) and Gameli Djokoto et al (2014). They all used different techniques but arrived at similar conclusions.…”
Section: Foreign Direct Investment and Agricultural Productionmentioning
confidence: 72%
“…Similarly, Oloyede (2014) using a Granger causality test found a positive relationship between FDI and agricultural sector development in Nigeria with data that spanned from 1981 to 2012. Other research works showed a positive relationship between FDI and agricultural output includes Kareem et al (2013) and Gameli Djokoto et al (2014). They all used different techniques but arrived at similar conclusions.…”
Section: Foreign Direct Investment and Agricultural Productionmentioning
confidence: 72%
“… Kim & Seo (2003) found a significant crowd-in effect of FDI on DI for the whole of Korea. In the long run, whilst Agosin & Machado (2005) ; Morrissey & Udomkerdmongkol (2012) and Mutenyo & Asmah (2010) reported crowding out effect of FDI on DI for Latin America, developing countries and sub-Saharan Africa respectively, Djokoto et al (2014) and Farla et al (2016) found the crowding-in effect of FDI on DI for Ghanaian agriculture and developing countries respectively. Babu (2021) found a crowding-out effect for India based on data from 1990/91 to 2014/15.…”
Section: Introductionmentioning
confidence: 99%
“…As the sector needs more investments for growth and development ( Hine, 2015 ; Primanthi, 2015 ), many countries have pursued policies to attract foreign direct investment (FDI) into the food manufacturing sectors of their respective economies to reap benefits including investment accumulation, technology transfer and job creation ( de Mello Jr, 1997 ; Farla et al, 2016 ; Kosova, 2010 ). Aside from these benefits, there is evidence that the inflow of FDI compliments domestic investment (DI) ( Farla et al, 2016 ; Mileva, 2008 ) or substitute DI ( Budang & Hakim, 2020 ; Oualy, 2019 ) for whole economy cases as well as the agricultural sector ( Djokoto et al, 2014 ). Agosin & Machado (2005) and Gallova (2011) have reported a neutral effect of FDI on DI.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations